Manajemen Kepemimpinan Kepala Madrasah dalam Membentuk Karakter Siswa di Era Digital MA NW Pengkelak Mas - Samsul Hadi; Ahmad Izzuddin; Aqis Mawaddah; Hijaziah Hijaziah; Sumiati Sumiati5 (PALAPA, 2024)
Advances in information and communication technology have opened wider access to knowledge and learning resources, but at the same time require the strengthening of students’ character so that they are able to face the challenges of the digital era wisely. This study aims to describe the leadership management of the madrasah principal in shaping students’ character in the digital era, as well as to identify the supporting factors, obstacles, and solutions implemented. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research informants consisted of the madrasah principal, teachers, and students. The results showed that the leadership of the madrasah principal was manifested through exemplary conduct, habituation, supervision, and the reinforcement of religious values. Supporting factors included teacher commitment, a religious madrasah environment, and structured religious programs, whereas the main obstacles stemmed from the negative influence of social media and the limited involvement of parents. The solutions implemented included a personal approach, strengthened supervision, and collaboration with parents in shaping students’ character. This study confirms that the effectiveness of the leadership management of the madrasah principal plays an important role in shaping students’ character in the digital era through the synergy of exemplary conduct, school culture, and family involvement.